The Female Avenger: Violence, Absurdity, and Black Humour in Roald Dahl's Short stories - ميساء حسام جابر (College of Education for Women, 2019)
Roald Dhal's is a prominent British short story writer who presented a fictional world full of contradictions and ironies. It is also full of double meanings where things are not what they appear to be and where meaninglessness is a prominent component. Dahl's world is also colored with blackness and grotesqueness; full of comedy that makes you shiver instead of laugh and characters who invite a sneak peek into a different side, a dark side of human nature. Dahl's themes are various and gripping but usually revolve around the triangle that frames his fiction: violence, humour, and absurdity. What seems to be a prominent and recurrent theme that intersects with every element in this triangle is revenge. In one story after another Dahl presents models of avengers. His female avenger is an image of a woman who is fixated on her revenge and who succeeds in her deeds regardless of the means she uses to exact her revenge. The female avenger in Dahl's short stories is a character who is ruthless and cunning in carrying out revenge against the male character, yet her action is often unexpected and shocking. This paper will address three of Dahl's stories that illustrate clear examples of female avengers. The discussion of selected short stories of Dahl will elaborate on the positioning of the female avenger in the midst of his recipe of black humour, absurdity, and violence.